C-Abl-p38α signaling pathway mediates dopamine neuron loss in trigeminal neuralgia. (June 2020) - Fu, Jia; Mu, Guo; Qiu, Ling; Zhao, Jiaomei; Ou, Cehua
Trigeminal neuralgia is a common neuropathic pain in the head and face. The pathogenesis of trigeminal neuralgia is complex, and so far, the pathogenesis of trigeminal neuralgia involving peripheral and central nervous inflammation theory has not been explained clearly. The loss of dopamine neurons in striatum may play an important role in the development of trigeminal nerve, but the reason is not clear. C-Abl is a nonreceptor tyrosine kinase, which can be activated abnormally in the environment of neuroinflammation and cause neuron death. We found that in the rat model of infraorbital nerve ligation trigeminal neuralgia, the pain threshold decreased, the expression of c-Abl increased significantly, the downstream activation product p38 was also activated abnormally and the loss of dopamine neurons in striatum increased. When treated with imatinib mesylate (STI571), a specific c-Abl family kinase inhibitor, the p38 expression was decreased and the loss of dopaminergic neurons was reduced. The mechanical pain threshold of rats was also improved. In conclusion, c-abl-p38 signaling pathway may play an important role in the pathogenesis of trigeminal neuralgia, and it is one of the potential targets for the treatment of trigeminal neuralgia.